HPLC ANALYSIS OF THE VITAMIN COMPOSITION OF THE AERIAL PARTS OF ANABASIS APHYLLA L. AND ITS ENDOPHYTES (Scientific journal of the Fergana State University, 2026)
This article presents a study on the water-soluble vitamin composition of the aerial parts of Anabasis aphylla L. and its endophytic fungi using high-performance liquid chromatography (HPLC). The research highlights the importance of investigating the chemical composition of plants and their endophytes as potential sources of bioactive compounds and vitamins. The findings provide valuable scientific and practical insights for applications in pharmaceuticals, food industry, and the development of biologically active supplements.